Netizen dan Cancel Culture: Studi Komunikasi Dakwah Gus Miftah - Setiawan, Rifki; Umami, Khairiza; Fadhilla, Ibnu; Maulidah, Mardhatillah; Suryadi, Doddy; Martian, Ferra (Jurnal komunikan, 2025)
This study analyzes the case of Cancel Culture that previously occurred in the context of Gus Miftah's da'wah communication. Through this event, it can be seen how quickly a statement can go viral and trigger various public reactions. This case highlights the importance of communication ethics, especially for public figures like Gus Miftah. On the one hand, cancel culture can be a tool to encourage social change, but on the other hand, this phenomenon also has the potential to damage the reputation of individuals and hinder constructive dialogue. This study concludes that in the digital era, religious leaders need to be more careful in communicating, while people need to develop better digital literacy to respond to various information circulating. The case of Gus Miftah is a valuable lesson about the importance of maintaining communication ethics in the context of da'wah and social life.